2015
DOI: 10.1016/j.appet.2014.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Rural Latino caregivers' beliefs and behaviors around their children's salt consumption

Abstract: Background Prevalence of high blood pressure has been increasing in U.S. children, with implications for long term health consequences. Sodium consumption, a modifiable risk factor for high blood pressure, is above recommended limits and increasing. Very little is known about Latino caregiver beliefs and behaviors around their children’s salt consumption. Methods In California’s Central Valley, qualitative interviews in Spanish investigated low-income caregivers’ views and understandings of their children’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
0
17
0
1
Order By: Relevance
“…Parents and caregivers can help lower sodium by influencing the way foods are produced, sold, prepared, and served [8]. Biologically, young children are more prone to choose and eat salty flavors, but this preference can be modeled by social factors, such as their parents feeding practices [9,10]. To promote salt reduction and consequently promote a healthy habit, parents of preschool-aged children were selected because early childhood is a lifespan stage where children learn about food and eating, while transitioning to an omnivore diet [11].…”
Section: Introductionmentioning
confidence: 99%
“…Parents and caregivers can help lower sodium by influencing the way foods are produced, sold, prepared, and served [8]. Biologically, young children are more prone to choose and eat salty flavors, but this preference can be modeled by social factors, such as their parents feeding practices [9,10]. To promote salt reduction and consequently promote a healthy habit, parents of preschool-aged children were selected because early childhood is a lifespan stage where children learn about food and eating, while transitioning to an omnivore diet [11].…”
Section: Introductionmentioning
confidence: 99%
“…This is an example of medical knowledge being interpreted by people to validate their pre-existing ideas about salt intake, health and illness[ 36 , 44 ]. It also could be that people prioritize taste over knowledge of detrimental effects of food in selecting foods to eat as found in other studies[ 45 ]. Most theories of health behavior propose that people who have a good understanding of biomedical knowledge tend to take action to use the knowledge to remain healthy[ 46 ].…”
Section: Discussionmentioning
confidence: 92%
“…As one of few studies that have investigated the acceptability of fluoridated salt for caries prevention in a US community, this study makes a modest but valuable contribution. It is one of very few examinations of how children’s caregivers use domestic salt and understand its properties [ 78 ]. Parental perceptions and actions based thereon are highly influential in oral health care seeking for children in minority communities, such as a low-income, rural Hispanic communities, which often have quite distinct oral health beliefs, understandings and responses [ 26 , 53 – 44 , 78 ], as well as a high prevalence of oral disease, especially among young children [ 12 , 19 – 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Benefits to children would be a powerful motivation for accepting and using this kind of salt product. Equally important from the perspective of the biomedical community, it would have to be demonstrated that fluoridated salt did not lead to an increased consumption of salt, a product with known (deleterious) cardio-vascular effects, especially but not exclusively in adults [ 78 ]. Most importantly, fluoridated salt would have to be perceived by the community to taste the same as non-fluoridated salt in order to be accepted for domestic use on a regular basis.…”
Section: Discussionmentioning
confidence: 99%